Women leaders : advancing careers - Brown, Genevieve; Irby, Beverly J.; Jackson, Shirley A. (Emerald Publishing Limited : Information Age Pub., 2012)
Women Leaders: Advancing Careers recognizes that while the majority of students enrolled in educational leadership preparation programs continue to be women; women's advancement to top school executive roles is still not comparable to that of men. Despite significant gains in the past decade, the biased treatment of women continues to be a barrier to their advancement to key administrative positions.The authors in Women Leaders: Advancing Careers have contributed significantly to the growing body of literature aimed at assisting the career advancement of women. Their research indicates that the concepts presented herein are critical to women's leadership preparations, advancement, and success. Women Leaders: Advancing Careers melds history, theory, research, and practice to provide guidance to aspiring women administrators in developing a career path and in attaining and successfully performing in executive roles.
Keywords: Women school administrators -- Selection and appointment -- United States.; Educational leadership -- United States.; Education -- Leadership.; Subject matter intended specifically for women and/or girls.; Educational strategies and policy.; elektronické knihy; electronic books